2005
DOI: 10.1093/pcp/pci135
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to Diverse Environmental Stresses Caused by a Suppression of Cytosolic Ascorbate Peroxidase in Tobacco BY-2 cells

Abstract: The active oxygen species (AOS) that arise from normal metabolic processes are kept under tight control by various antioxidant mechanisms. AOS are important signal molecules that regulate many physiological processes, including environmental stress responses. In this work, we have investigated the effect of lowered cytosolic ascorbate peroxidase (APX) activity in transgenic tobacco BY-2 cells, using two transformed BY-2 cell lines, cAPX-S2 and cAPX-S3, resulting from co-suppression by expression of Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…It has been reported that a wide range of environmental stresses cause the enhanced production of ROS in plant cells (Bowler et al, 1992;Foyer et al, 1994;Alscher et al, 1997;Shigeoka et al, 2002;Mittler et al, 2004;Ishikawa et al, 2005;Miller and Mittler, 2006;Al-Taweel et al, 2007). The overexpression of GolS1 or GolS2 also conferred tolerance to salinity or chilling stress ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a wide range of environmental stresses cause the enhanced production of ROS in plant cells (Bowler et al, 1992;Foyer et al, 1994;Alscher et al, 1997;Shigeoka et al, 2002;Mittler et al, 2004;Ishikawa et al, 2005;Miller and Mittler, 2006;Al-Taweel et al, 2007). The overexpression of GolS1 or GolS2 also conferred tolerance to salinity or chilling stress ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured transgenic tobacco cells with lowered cAPX activity due to co-suppression showed greater tolerance to environmental stress, such as heat and salinity, than wild-type cells. 7) This tolerance was accompanied by activation of a specific protein kinase and upregulation of the expression of stress-responsive genes including HSP as well as increased cellular ROS accumulation. Pnueli et al 95) have also demonstrated that cAPX (APX1)-knockout Arabidopsis plants showed upregulation of the expression of various genes, including those for stressrelated proteins and transcription factors.…”
Section: Role Of Capx In Redox Signal Modulationmentioning
confidence: 99%
“…6) Meanwhile, convincing evidence of the involvement of APX in the regulation of redox signal transduction is also accumulating. 7,8) This review focuses on recent advances concerning the physiological function and molecular properties of APX isoenzymes in photosynthesizing organisms. In addition, the pathway of AsA biosynthesis is highlighted, given the recent elucidation of the entire D-mannose (D-Man)/L-galactose (L-Gal) pathway in plants.…”
mentioning
confidence: 99%
“…Stress acclimation is often triggered by minor environmental changes and results in an enhanced protection against a subsequent more severe stress [2][3][4]. Such an enhanced stress resistance may be confined to the stress that triggers acclimation or it may provide cross-protection also against other forms of stress [5][6][7]. In order to acclimate, plants need to monitor and sense continuously their environment.…”
Section: Introductionmentioning
confidence: 99%